EU strategy on counter terrorism: Steps towards a coherent network policy - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2006)
The EU Counter-Terrorism Strategy, which was adopted by the European Council in December 2005, reflects the EU's aim of forming a network of the member states' foreign and domestic policies in the fight against terrorism. The accompanying action plan contains 160 separate measures in the four strands of work of the EU strategy (prevent, protect, pursue and respond). The main objective of this EU policy is to confront "the networks of terror with networks against terror".The EU Counter-Terrorism Strategy acts as a significant driving force in European network building, however not in the sense of communitarisation. Weaknesses in horizontal, institutional and vertical coherence in forming a network of European foreign and domestic polices will only be resolved in the medium and long term.Ideas to create a European CIA, a Directorate General for Homeland Security or the introduction of a supranational police and public prosecution office did not take hold. A harmonisation of member states' policies along these lines seems therefore unrealistic at present. The member states continue to be the fundamental pillars of the European networking process.In order to secure progress in European co-operation which has already been achieved, the added value of a European network should be increased substantially for national policies and the EU strategy needs to align prevention more strongly as a cross cutting task of fighting terrorism. (SWP-Research Papers / SWP)
Keywords: 320